AB0365 The insulin resistance, metabolic syndrome and type 2 diabetes mellitus development risk assessment in rheumatoid arthritis patients. (12th June 2018) - Kondratyeva, L.; Popkova, T.
Abstract : Background: The insulin resistance (IR) is the known risk factor of type 2 diabetes mellitus (DM) and potential cardiovascular complications. But it's not feasable in routine practice to calculate special indices to determine IR, as insulin levels monitoring is not a standard procedure in RA pts. Metabolic syndrome (MS) criteria and questionnaires designed to assess the risk of DM development can help to differentiate a subgroup of pts, requiring more accurate evaluation of their IR status. Objectives: To determine how IR relates with MS and DM development risk assessment in RA patients. Methods: A total of 46 RA pts (39 women, 7 men, 57 [39; 64] years old) without established DM were enrolled in the study, including 14 pts with IR and 32 pts without IR, matched by age and sex. IR was defined as Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) index >2, 77. National Cholesterol Education Program/Adult Treatment Panel III (NCEP/ATPIII) and International Diabetes Federation (IDF) criteria were used to confirm MS. The abdominal obesity was determined as waist circumference (WC) ≥80 cm for women and ≥94 cm for men (by IDF), and WC ≥88 cm for women and ≥102 cm for men (by NCEP/ATPIII). If the total score of questionnaire Finnish Type 2 Diabetes Risk Assessment Form (FINDRISK) was ≥12, the DM development risk was considered as moderate or high. Results: The body mass index was higher in pts with IR than in those without IR (28, 5 [24, 8; 32, 5 kg/m 2 vs 22, 4 [20, 1; 25, 4 kg/m 2, p < 0, 001). Abdominal obesity was documented in 100% pts with IR and in 41% pts without IR by IDF criteria (p=0, 002), in 64% and 22% pts, respectively, by NCEP/ATPIII criteria (p=0, 01). There were no differences in DAS28, CRP and ESR values and glucocorticoids users proportions. MS by IDF criteria was diagnosed in 57% pts with IR and 19% pts without IR (p=0, 02), and MS prevalence by NCEP/ATP III criteria was similar in both groups (36% vs 16%, respectively, p=0, 2). Higher rates of moderate and high risk for DM development were found in pts with IR compared to pts without IR (71, 4% vs 31, 2%, p=0, 03). Conclusions: The FINDRISK and IDF questionnaires, but not the NCEP/ATP III criteria of MS, can be helpful in selecting RA pts with potential IR. Abdominal obesity was the key factor indicative of IR in RA pts. On the other hand, IR may not be there even in the presence of several traditional DM risk factors. Therefore further clarification of potential contribution of RA-related risks is needed. Disclosure of Interest: None declared